Research on the Narrative Strategies and Effects of International Communication of New Mainstream Films: Data Analysis based on YouTube Platform - Xu, Huixin; Chen, Yiyu (International Journal of Social Sciences and Public Administration, 2024)
The new mainstream film is a new form of the current film, which plays an important role in the international narrative communication. According to the YouTube film transmission data in the platform, a comprehensive analysis of the current new mainstream film in the international narrative strategy, including increasing the film transmission themes, improve the film design imagination, add continuity characters and change spread thinking, according to the relevant movie data, confirm the film international narrative communication effect, for the spread of sustainable proposals.